First report of baby crab molecular identification from the North Coast of Cirebon, Indonesia - Achmad Mufidh Karohmatullah; Aninditia Sabdaningsih; Suradi Wijaya Saputra; Fitria Sari (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Baby crab consumption has become a growing trend in snack markets across Asia, with rising popularity in at least five countries. Cirebon, situated on the coast of West Java, is a region experiencing particularly high demand for baby crab commodities, notably the locally known